(untitled) (Progressive Agriculture, 2013)
Acetone extracts of red chili (Capsicum frutescens), garlic (Allium sativum) and neem (Azadirachta indica) were used to evaluate their insecticidal effects against a dry fish beetle, Dermestes sp. larvae and a mite, Necrobia sp. adult. The concentration of plant extracts were 60, 80 and 100% for Dermestes sp. larvae and 10, 15 and 20% for Necrobia sp. adult. The mortality of Necrobia sp. at 24, 48 and 72 hours after treatment (HAT) indicated that red chili extract possessed the highest insecticidal effect followed by neem and garlic. Mortality was found to be directly proportional to the concentration of plant extracts. For Necrobia sp. (adult) LC50 values of red chili, neem and garlic were 0.78, 0.85 and 1.68%, respectively at 24 HAT. Red chili was found to possess the highest insecticidal effect among these three with the highest toxic effect at 48 HAT (0.29%) and 72 HAT (0.03%). For the larvae of Dermestes sp., the LC50 values of red chili was 0.60%, neem 0.69% and garlic 1.15% at 24 HAT, again indicating that red chili had the highest insecticidal effect on dry fish insects. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16756 Progress. Agric. 21(1 & 2): 93 - 103, 2010